Kinetics of acetic acid-enhanced coarse limestone dissolution. (1st January 2014) - Liu, Shengyu; Qiu, Wei; Nengzi, Lichao; Lu, Chengwei; Qu, Bing; Xu, Yuanyuan
The dissolution kinetics of limestone with organic acid additives was studied by pH-stat method. The results showed that the control step of limestone dissolution was changed with pH changing. At same time, the particle size of limestone was an important effect on its dissolution control step too. Enhancement coefficient of limestone dissolution added acetic acid was the function of pH and concentration of acetic acid. By applying the shrinking core model a kinetic model for the limestone dissolution process was fitted to experimental results, which was function of concentration of acetic acid, particle of limestone and pH value and temperature.